A narrative synthesis of the applicability of the CaR–FA–X model in child and adolescent populations: a systematic review. Issue 9 (21st October 2017) - Stewart, Tracy M.; Hunter, Simon C.; Rhodes, Sinéad M.
ABSTRACT: The CaR–FA–X model [Williams, J. M. G., Barnhofer, T., Crane, C., Hermans, D., Raes, F., Watkins, E., … Dalgleish, T. (2007). Autobiographical memory specificity and emotional disorder. Psychological Bulletin, 133 (1), 122–148. doi:10.1037/0033-2909.133.1.122 ] is the most prominent and comprehensive model of overgeneral autobiographical memory (OGM) and provides a framework for OGM. The model comprises of three mechanisms, capture and rumination, functional avoidance and impaired executive control. These can independently, or in interaction, account for OGM. This systematic review aims to evaluate the existing research on the CaR–FA–X model, and trauma exposure studies specific to child and adolescent populations. The following databases were searched: "PsychInfo", "PsychArticles", "PubMed", "Web of Science", "Medline", "SCOPUS" and "Embase" for English-language, peer-reviewed papers with samples < M = 18 years, published since 1986. Support was reported for a relationship between trauma exposure and OGM as well as for capture errors and OGM. Limited support was found for rumination, avoidance and impaired executive control in isolation. No support was found for interacting mechanisms and OGM. Partial support for the CaR–FA–X model was found for child and adolescent populations. Recommendations, proposals for future research and plausible explanations for the mixed findings are discussed.